2020
DOI: 10.1002/cti2.1203
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab monotherapy uncovered the role of the CCL22/17‐CCR4+ Treg axis during remission of crescentic glomerulonephritis

Abstract: Objectives Tocilizumab (TCZ) is a humanised anti‐interleukin (IL)‐6 receptor (IL‐6R) monoclonal antibody that is a promising agent to treat various autoimmune diseases. However, the mechanism of TCZ efficacy is unclear. This study aims to elucidate the relationship between Tregs and IL‐6R blockade in autoimmunity‐mediated renal disease based on a TCZ‐treated cohort of patients with anti‐neutrophil cytoplasmic antibody (ANCA)‐associated vasculitis (AAV) and in an experimental model of crescentic gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Musante et al [437], Han et al [438], Zhang et al [439], Sato et al [440], Yang et al [441], El-Aouni et al [442], Perisic et al [443], Chung et al [444], Wilkening et al [445], Kahvecioglu et al [446], Hu et al [447] and Worthmann et al [448] revealed that ALB (albumin), KLF15, ATF3, LPL (lipoprotein lipase), CUBN (cubilin), ILK (integrin linked kinase), PLEKHH2, TNF (tumor necrosis factor), CCR2, SPON2, LRRC55 and IGFBP1 might be the potential targets for FSGS diagnosis and treatment. Alves et al [449], Ma et al [450], Esposito et al [451], Ai et al [452], Lu et al [453], Bui et al [454], Bao et al [455], Zuo et al [456], Su et al [457], Wang et al [458], Šalamon et al [459], Harskamp et al [460], Ćwiklińska et al [461], Hishida et al [462], Gunay-Aygun et al [463], Simpson et al [464], Svenningsen et al [465], Wang et al [466], Rao et al [467], Chen et al [468], Bedin et al [469], Cao et al [470], Jang et al [471], de Frutos et al [472], Lin et al [473], Wang et al [474], Liu and Zhuang [475], Feng et al [476], Yu et al [477], Reed et al [478], Milillo et al [479], Chen et al [74], Chen et al [480], Vieira et al [76], Charlton et al [481], Shi et al [482], Zhou et al [483], Nazari et al [241], Greene et al [484], Lazar et al [485], Jobst-Schwan et al [486], Du et al [487], Liu et al [85], Liu et al [488], Liu et al [489], Lee et al [490], Wen et al [491], Sakai et al [492], Zhang et al [493], Wang et al [494], CD5L Castelblanco et al [251], Chen et al [495], Swanson et al [496], Ksiazek, [497], Li et al [498], Zhang et a...…”
Section: Discussionmentioning
confidence: 99%
“…Musante et al [437], Han et al [438], Zhang et al [439], Sato et al [440], Yang et al [441], El-Aouni et al [442], Perisic et al [443], Chung et al [444], Wilkening et al [445], Kahvecioglu et al [446], Hu et al [447] and Worthmann et al [448] revealed that ALB (albumin), KLF15, ATF3, LPL (lipoprotein lipase), CUBN (cubilin), ILK (integrin linked kinase), PLEKHH2, TNF (tumor necrosis factor), CCR2, SPON2, LRRC55 and IGFBP1 might be the potential targets for FSGS diagnosis and treatment. Alves et al [449], Ma et al [450], Esposito et al [451], Ai et al [452], Lu et al [453], Bui et al [454], Bao et al [455], Zuo et al [456], Su et al [457], Wang et al [458], Šalamon et al [459], Harskamp et al [460], Ćwiklińska et al [461], Hishida et al [462], Gunay-Aygun et al [463], Simpson et al [464], Svenningsen et al [465], Wang et al [466], Rao et al [467], Chen et al [468], Bedin et al [469], Cao et al [470], Jang et al [471], de Frutos et al [472], Lin et al [473], Wang et al [474], Liu and Zhuang [475], Feng et al [476], Yu et al [477], Reed et al [478], Milillo et al [479], Chen et al [74], Chen et al [480], Vieira et al [76], Charlton et al [481], Shi et al [482], Zhou et al [483], Nazari et al [241], Greene et al [484], Lazar et al [485], Jobst-Schwan et al [486], Du et al [487], Liu et al [85], Liu et al [488], Liu et al [489], Lee et al [490], Wen et al [491], Sakai et al [492], Zhang et al [493], Wang et al [494], CD5L Castelblanco et al [251], Chen et al [495], Swanson et al [496], Ksiazek, [497], Li et al [498], Zhang et a...…”
Section: Discussionmentioning
confidence: 99%
“…CD8α+ DCs are recognized to be distinct and most efficient in their capability for cross presentation, unique from non-CD8+ DCs [ 20 ] permitting antigen presentation for induction of tolerance [ 21 ]. IL-6 blockade leading to increased Treg and immune tolerance [ 22 ] or through M2 macrophages have been described [ 23 ]. We demonstrate here a novel aspect of peripheral tolerance through CD8α+IL10+ cDCs triggered by tocilizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Correlative studies associating improvement of CCR4 + FOXP3 + Treg cell frequencies with drug-free remission have supported the concept that ultimately, Treg cell frequencies are sensitive markers of the inflammatory status ( 152 ). In a mouse model, blocking IL-6 activity ameliorated the disease and increased the migration of Tregs into the kidney and the regional lymph nodes ( 152 ). In both GPA and MPA, B cell depletion therapy and conventional immunosuppressants yielded similar CD4 + Treg cell numbers ( 153 ).…”
Section: Regulatory T (Treg) Cellsmentioning
confidence: 97%
“…Inhibition of tryptophan degradation enhances immune responsiveness, with a tendency to more severe glomerulonephritis (151). Correlative studies associating improvement of CCR4 + FOXP3 + Treg cell frequencies with drugfree remission have supported the concept that ultimately, Treg cell frequencies are sensitive markers of the inflammatory status (152). In a mouse model, blocking IL-6 activity ameliorated the disease and increased the migration of Tregs into the kidney and the regional lymph nodes (152).…”
Section: Antineutrophil Cytoplasmic Antibody (Anca)-associated Vascul...mentioning
confidence: 99%